Pakistan Foreign Policy and South America: An Avenue for Influence and Interest - Prof. Dr. Omar Farooq Zain,; Shahid, Talha; Asma Faridi, (Journal of Peace, Development and Communication, 2024)
Fragmentation of the bipolar World in the 1990s after the demise of the Soviet Union proved a decisive event for establishing US hegemony in the World. But in the decade just after the Cold War, the transition of World Order started with widening cuts in the US hegemony and distribution of power among developing and emerging economies of the world. The US hegemonic position was, no doubt, challenged by the policy of invasion, or what Noam Chomsky called Preventive War[1], in different countries in the following decades, global financial crisis of 2007-08, and then the pandemic. But some regions of the world, such as Latin America, not only managed these crises efficiently with low rates of debts, but also maintained its fiscal and macroeconomic position along with enhancement in economic growth rates of states, interaction among states in investment sector along with boom in national markets. 441 million people inhabit Latin America4 which consists of 12 countries[2]. Contributing to the world economy with a share of 6.4 trillion US Dollars GDP[3]. This area, abundant of natural resources, energy generation capacities, water resources and biodiversity, is an alluring center of focus for the Western developed economies and particularly Asian giants and emerging economies of the world. This article elaborates the importance of Latin America and how Pakistan can gain benefits from that region.